2022
DOI: 10.55563/clinexprheumatol/4dg0or
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tocilizumab in the management of COVID-19: a systematic review and meta-analysis of observational studies

Abstract: Objective. This systematic review and meta-analysis was aimed to evaluate the efficacy and safety of tocilizumab (TCZ) in treating severe coronavirus disease 2019 . Methods. The electronic search was made using PubMed, Scopus, CEN-TRAL, and Google scholar to identify the retrospective observational reports. The studies published from 01 January 2020 to 30th October 2020. Participants were hospitalised COVID-19 patients. Interventions included tocilizumab versus placebo/standard of care. The comparison will be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…In the COVID-19 era, infection control measures inevitably failed as the need to deal with an unprecedented health emergency arose [5]. Although the role of extensive use of immunosuppressants such as steroids, anti-IL1 and above all tocilizumab, is still debated, it could be speculated that it may have contributed to alter the balance of immune defenses by favoring the development of superinfections [18]. Some available evidence in literature, like the work published by Giacobbe et al, which includes all ICU admitted patients, seems to consider steroids and tocilizumab use as a factor associated to an increased risk of BSI development [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the COVID-19 era, infection control measures inevitably failed as the need to deal with an unprecedented health emergency arose [5]. Although the role of extensive use of immunosuppressants such as steroids, anti-IL1 and above all tocilizumab, is still debated, it could be speculated that it may have contributed to alter the balance of immune defenses by favoring the development of superinfections [18]. Some available evidence in literature, like the work published by Giacobbe et al, which includes all ICU admitted patients, seems to consider steroids and tocilizumab use as a factor associated to an increased risk of BSI development [10].…”
Section: Discussionmentioning
confidence: 99%
“…They found that there was no significant difference in the risk of VTE between patients with COVID-19 who received immunomodulatory agents and those who received standard care (OR 0.52, 95%CI 0.22–1.20; I 2 = 6%) 22 . In addition, Viswanatha et al 21 in a meta-analysis that included 5686 patients with COVID-19 has shown a non-significant difference in the occurrence of pulmonary embolism during the TCZ therapy compared to the standard of care (OR 1.01, 95%CI 0.45–2.26, I 2 = 0%). Likewise, our analysis did not find any significant increase in the risk of thrombosis for patients with COVID-19 who were treated with TCZ.…”
Section: Discussionmentioning
confidence: 99%
“…While outcomes that were more subjectively measured, such as disease activity, were thought to be susceptible to bias 23 . Moreover, the Viswanatha et al 21 meta-analysis found that TCZ therapy was associated with a lower risk of mortality compared to the standard of care (OR − 0.11, 95%CI − 0.18 to − 0.04), but with significant heterogeneity among studies (I 2 = 88%, p = 0.001). Similarly, our study revealed that the use of TCZ was associated with a lower risk of mortality in critically ill patients when compared to the standard care; patients treated with TCZ had a 43% lower risk of 30-day mortality and a 33% lower risk of in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tocilizumab (TCZ) is a humanized monoclonal antibody against the interleukin-6 receptor (IL-6R), applied in severe COVID-19 with hyperinflammation since early 2020 [ 19 , 20 , 21 ]. It was proven to reduce in-hospital mortality, the need for mechanical ventilation, or intensive care unit (ICU) transfer [ 22 , 23 , 24 , 25 , 26 ]. It was approved for use in COVID-19 by the European Medicines Agency (EMA) in December 2021 and one year later by the Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%